The Effects of P, S and Mg Supplementation of Oil Palm Fronds Fermented by Phanerochaete chrysosporium on Rumen Fluid Characteristics and Microbial Protein Synthesis - Febrina, Dewi; Jamarun, Novirman; Zain, Mardiati; Khasrad (Pakistan Journal of Nutrition, 2016)
The objective of this study was to evaluate the effects of sulfur, phosphorus and magnesium supplementation of oil palm fronds fermented by Phanerochaete chrysosporium on rumen fluid characteristics and microbial protein synthesis. This research was carried out using a randomized block design with 4 treatments and 4 replications. The following treatments were performed: A = fermented oil palm fronds (FOPFs); B = FOPFs+0.4% P; C = FOPFs+0.4% P+0.3% S and D = FOPFs+0.4% P+0.3% S+0.1% Mg. The data were subjected to analysis of Variance (ANOVA) and differences between treatments were tested using Duncan’s Multiple Range Test (DMRT). The observed parameters were microbial protein synthesis and rumen fluid characteristics. Supplementation of FOPFs with P, S and Mg resulted in the highest microbial protein synthesis and VFA concentration.